Gambaran Tingkat Kepuasan Ibu Bersalin Di Ruang VK Menggunakan BPJS Di RSUD BANJARBARU Tahun 2015 - Nina Rahmadiliyanii; Hj. Saidatunnisa; Nina Mastuti; STIKES Husada Borneo; Puskesmas Sei Lulut; Alumni STIKES Husada Borneo (HB PRESS, 2016)
According to the basic health research in 2010, childbirths assisted by midwives in poor target groups reached approximately 69.3%. While childbirth is performed by health workers in health facilities reached 55.4%. One important obstacle to access childbirths assisted by midwives in health facilities is limitations and unavailability of cost so that makes breakthrough policy to improve the childbirth helped by health workers in health facility through a policy called assurance of childbirth. The assurance of childbirth is intended to eliminate the financial barriers for pregnant women toobtain childbirthassurance, which includes pregnancy examination, childbed care including family planning after childbirth, andnewborn care. This study aims to determine description of the rate of childbirth satisfaction using BPJS services in regional public hospital of Banjarbaru 2015. Thisresearchusesdescriptive methodwith cross sectional approach. The research samplesare 50 respondents with Non-Probability Sampling techniques by accidental sampling. The results showed the satisfaction level of childbirth is 81.5% satisfied, BPJS service in regional public hospital of Banjarbaru. ,50 respondents use childbirth assurance card of BPJS. From these results it can be concluded that the description of the rate of childbirth satisfaction using BPJS in hospitals Banjarbaru BPJS 2015 generally said satisfied.